1998
DOI: 10.1136/jcp.51.1.55
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and histological associations of cagA and vacA genotypes in Helicobacter pylori gastritis.

Abstract: Aims-To determine the relation among the cytotoxin associated gene (cagA) and vacuolating cytotoxin gene (vacA) status of Helicobacter pylori isolates, the associated clinical diseases, and the severity and pattern of chronic gastritis. Methods-Helicobacter pylori was cultured from gastric biopsies obtained from dyspeptic patients. DNA was extracted from the isolates and the cagA and vacA status determined by the polymerase chain reaction (PCR). The prevalence of the diVerent cagA and vacA genotypes in three c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
64
1
11

Year Published

1999
1999
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(89 citation statements)
references
References 24 publications
13
64
1
11
Order By: Relevance
“…Protein CagA is the most investigated H. pylori virulence factor, but its connection with the presence of various mucosal histological changes is still controversial and there are many studies with contradictory results (30)(31)(32)(33). Our results are consistent with previous observations, in which CagA elicited high neutrophil accumulation, measured as inflammation activity in gastric mucosa (29).…”
Section: Discussionsupporting
confidence: 83%
“…Protein CagA is the most investigated H. pylori virulence factor, but its connection with the presence of various mucosal histological changes is still controversial and there are many studies with contradictory results (30)(31)(32)(33). Our results are consistent with previous observations, in which CagA elicited high neutrophil accumulation, measured as inflammation activity in gastric mucosa (29).…”
Section: Discussionsupporting
confidence: 83%
“…Here, 73.2% of the H pylori strains were cagA-positive, a prevalence similar to that reported in many studies from Western countries (e.g. USA, 60% [7] ; Spain, 66% [26] ; and England, 68% [27] ) but lower than that reported in some East Asian studies, which encountered over 90% of cagApositive isolates (Table 4) [25,28] . In addition, a highly significant correlation was observed between cagA status and vacAs1 and vacAs1m1 genotypes (Table 2), which is commonly linked to an increase in H pylori virulence [13,14,29,30] .…”
Section: Vaca Allelesmentioning
confidence: 64%
“…Moreover, a high frequency of cagA-positive strains was observed in DU patients ( Table 3), indicating that a statistical association could be reached by increasing the number of patients in future studies. [14,23,26,27] 66-73 [14,23,26,27] 34-72 [13,14,34] America 57-68 16-48 37-44 29-63 [19,20,24] 57-75 [7,19,24] 46-69 [24,32] East Asia 100 0 41-94 5-55 [12,25,28] 90-100 [12,25,28,35] 80-100 [12,21,35] Torres…”
Section: Vaca Allelesmentioning
confidence: 99%
“…Our study population is rather young but, even so, we demonstrated that glandular atrophy, neutrophil activity, and OLGA stages were significantly higher in older patients. Infection generally occurs during childhood and development of more severe histopathological manifestations, such as intestinal metaplasia and glandular atrophy, are linked to prolonged infection and consequently to patients' age [25,26]. A study performed in the northern part of the country also revealed that patients with atrophic gastritis were significantly older than the ones with no atrophy [5].…”
Section: Discussionmentioning
confidence: 99%